System requirements engineering by V. Loucopoulos and V. Karakostas : 1995.- McGraw-Hill International series in Software Engineering. ISBN 0-07-707843-8 - Thomas, Pablo Javier (2001)
Requirements Engineering is the key issue for the development of Software Systems, that meet the expectations of their customers and users, are delivered on time, and are developed within budget. This book intends to provide the state of the art material on techniques, methods, and tools for the elicitation, representation and validation of requirements.